2016
DOI: 10.1093/eurheartj/ehv690
|View full text |Cite
|
Sign up to set email alerts
|

Coronary plaque quantification and fractional flow reserve by coronary computed tomography angiography identify ischaemia-causing lesions

Abstract: AimsCoronary plaque characteristics are associated with ischaemia. Differences in plaque volumes and composition may explain the discordance between coronary stenosis severity and ischaemia. We evaluated the association between coronary stenosis severity, plaque characteristics, coronary computed tomography angiography (CTA)-derived fractional flow reserve (FFRCT), and lesion-specific ischaemia identified by FFR in a substudy of the NXT trial (Analysis of Coronary Blood Flow Using CT Angiography: Next Steps).M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
147
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 268 publications
(171 citation statements)
references
References 34 publications
20
147
3
1
Order By: Relevance
“…FFRCT <0.80 was considered diagnostic of lesion specific ischaemia. A report said that low-density non-calcified plaque (LD-NCP) and FFRCT yielded diagnostic improvement over stenosis assessment with AUCs increasing from 0.71 by stenosis 50% to 0.79 and 0.90 when adding LD-NCP ≥30 mm 3 and LD-NCP ≥30 mm 3 + FFRCT ≤0.80, respectively (24). However, whether CCTA image can display the actual vascular elasticity still needs to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…FFRCT <0.80 was considered diagnostic of lesion specific ischaemia. A report said that low-density non-calcified plaque (LD-NCP) and FFRCT yielded diagnostic improvement over stenosis assessment with AUCs increasing from 0.71 by stenosis 50% to 0.79 and 0.90 when adding LD-NCP ≥30 mm 3 and LD-NCP ≥30 mm 3 + FFRCT ≤0.80, respectively (24). However, whether CCTA image can display the actual vascular elasticity still needs to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that the presence of high-risk plaque features, especially large low attenuation plaque, a CTA surrogate for necrotic core, is strong predictor of FFR-verified ischemia independent of degree of luminal stenosis. 102,103 Local impairment of the vessel to dilate at the site of a stenosis with either a large plaque burden or necrotic core, a hallmark of vulnerable plaque, may contribute to ischemia independent of the degree of luminal narrowing. In this regard, plaques with large necrotic cores are often significantly positively remodeled, even if the lumen is not significantly narrowed.…”
Section: Discussionmentioning
confidence: 99%
“…19 The presence of low-density non-calcified plaque (≥30 mm 3 ) and FFR CT (≤0.80) increased significantly the diagnostic accuracy of coronary stenoses to detect lesion-specific ischemia (as assessed by invasive FFR), documented by an increase in the area under the receiver operating characteristic curve from 0.71 to 0.90 (P < 0.001). The non-randomized Prospective LongitudinAl Trial of FFR CT : Outcome and Resource IMpacts (PLATFORM) trial assessed the impact of FFR CT on clinical outcomes, downstream resource utilization and costs in two parallel observational arms, one with an intended invasive strategy (n = 380) and one with planned non-invasive testing (n = 204).…”
Section: The Better Evaluation Of Acute Chest Pain With Computedmentioning
confidence: 92%